2014
DOI: 10.1159/000354336
|View full text |Cite
|
Sign up to set email alerts
|

Course of Hemoglobin and Hematocrit during and after Preparatory Plasmaphereses without and with Infusion of NaCl 0.9% 500 ml

Abstract: Background: The aim of this study was to evaluate the course of hemoglobin (HGB) concentration and hematocrit (HCT) in donor blood during and after preparatory plasmaphereses (PP) without NaCl and with an infusion of 500 ml 0.9% NaCl during PP. Methods: After informed consent 32 plasma donors were studied in a crossover design. They underwent PP once without NaCl infusion and once, on a different day, with infusion of 500 ml 0.9% NaCl. HGB concentration and HCT values in donor blood were analyzed using a Sysme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 7 publications
2
34
1
Order By: Relevance
“…Literature search reveals insignificant decline or increase in hemoglobin values after single TPE session, and after intensive plasma donation of 1 L/day for 5 consecutive days. 16,22 Red blood cell loss in tubing in a single TPE session is ~11 mL. 23 To explain the discrepancy with earlier findings, fluid balance was used as a predictor for the day-to-day difference in hemoglobin and it was found that 1000 mL increase in balance reduced the hemoglobin by a factor of 0.61 (p = 0.025), and thus hemodilution is the likely cause for the observed decrease in hemoglobin in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…Literature search reveals insignificant decline or increase in hemoglobin values after single TPE session, and after intensive plasma donation of 1 L/day for 5 consecutive days. 16,22 Red blood cell loss in tubing in a single TPE session is ~11 mL. 23 To explain the discrepancy with earlier findings, fluid balance was used as a predictor for the day-to-day difference in hemoglobin and it was found that 1000 mL increase in balance reduced the hemoglobin by a factor of 0.61 (p = 0.025), and thus hemodilution is the likely cause for the observed decrease in hemoglobin in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…It was based on three studies: an observation of saline infusion in donors with severe drops in blood pressure at DP, 2 and two crossover trials of 32 repeat plasma donors each on saline infusion 500 ml in divided doses after each cycle during DP. 3,4 DP was performed with the automated plasma collecting system (PCS2, Haemonetics) via a single needle technique. It operates in a discontinuous flowmanner with 4-5 repetitive cycles of draw and collection phases alternating with return phases.…”
mentioning
confidence: 99%
“…First hemoglobin values before plasmapheresis were set to 100%. The duration of plasmapheresis is stretched from 0 to 1 hours and values at 48 hours were interpolated 4 In trial 1, there was a reduction of IgG concentration in collected plasma related to the average IgG serum concentration referred to as yield % without saline to 85.5% vs to 80.5% with saline (P < .001) as given in Table 1. 3 In trial 2, there was an important 11% to 12% increase of the donor hematological values without saline during DP as shown in Figure 1.…”
mentioning
confidence: 99%
“…volemic events during PP, an infusion of NaCl 0.9% 500 ml should be given during PP [3,4]. If saline infusion was given after PP the loss of red cell mass with the tubing system could be reduced from 12,0 ml to 1,3 ml per donation on average [5].…”
mentioning
confidence: 99%
“…However, the disadvantage of this method is that hypovolemic events cannot be prevented during PP. On the other hand, if 500 ml NaCl 0.9% is given step-by-step after each cycle during PP [4], there may not be enough NaCl 0.9% solution at the end of PP ( 100 ml) to re-infuse all the blood in the tubing system to the donor body.…”
mentioning
confidence: 99%